Aesthetics of Space in Nineteenth-Century British Literature, 1843-1907 - Giles, Whiteley
Uncovers the link between Ruskin and the tradition of the aesthetics of spaceDiscusses a hitherto under-researched tradition of city-writing, linking Ruskin to modernismReads comparatively five important mid to late nineteenth-century writersMarries close textual analysis with historically and geographically informed contextFills a gap in the critical literature on city-writing between realism and early modernismCharting an 'aesthetic', post-realist tradition of writing, this book considers the significant role played by John Ruskin's art criticism in later writing which dealt with the new kinds of spaces encountered in the nineteenth-century. With chapters devoted to the ways in which aesthetic and decadent writers such as Walter Pater and Oscar Wilde built upon and challenged Ruskin's ideas, the book links the late Dickens to the early modernism of Henry James. The Aesthetics of Space in Nineteenth-Century British Literature gives a vibrant vision of what an aesthetically sensitive treatment of these spaces looked like during the period.